Electrical characteristics and clinical outcomes during left bundle branch area pacing in patients with narrow QRS and comparison in mechanical synchrony with his bundle pacing, biventricular pacing and right ventricular apical pacing - Chow, Han Bing; Chan, S. T.; Ho, Y. H.; CARYN, T. J.; LING, H. S.; Chan, En Ze; Chung, B.K.; LEONG, L. K.; Thien, L.K.; Pang, I. X.; Khor, H. K.; Tan, C.T.; et al. (Elsevier Inc, 2023)
Conduction system pacing preserves physiological electrical synchrony in comparison to conventional right ventricular apical pacing (RVAP). Left bundle branch area pacing (LBBAP), an alternative modality to His Bundle Pacing (HBP) has been recently reported to have higher implant success rates, stable electrical parameters, and fewer lead-related problems. Limited evidence demonstrated that LBBAP may circumvent the technical and electrophysiological difficulties encountered in His bundle